al-ghadir fi al kitab wa-al sunnah wa-al-adab - Amīnī, ʻAbd al-Ḥusayn Aḥmad (Maktabat al-Imam Amir al-Mu'minin 'Alayh al-Salām al-'Ammah, 1976)
On the festival of Ghadīr, celebrated by the shiites to commemorate the appointment of 'Ali-ibn Abi Talib, Calipn, 600 (ca.)-661, as Prophet M<uhammad's successor; Shiite viewpoint.